Gêneros textuais : análise das sequências argumentativas prototípicas nos editoriais do jornal "O Popular" - Gomes, Fernanda Martins da Costa (2021)
This research aims to describe the organization of prototypical argumentative sequences in editorials based on the approximation of their rhetorical units and the macropropositions that constitute the argumentative textual sequence. Thus, it seeks to analyze and describe how the prototypical argumentative textual sequences, which are cognitive categories and cultural products constructed by the subjects in the interaction (ADAM, 2008), are organized in this textual genre. To this end, the study is based on the theoretical notes Theory of Textual Genres (BAKHTIN, 1992, 2010; BEZERRA, 2009; MARCUSCHI, 2002, 2008; ROJO, 2005; MOTTA-ROTH; 2005; BONINI, 2005; RODRIGUES, 2005; MILLER 2009; BAZERMAN, 2005) and textual sequences (ADAM, 2005, 2008, 2019; BRONCKART, 1999; SOUSA, 2012). In this sense, the investigation, based on a qualitative analysis, maps the prototypical textual sequences of the editorials; it highlights the functional relationship between rhetorical units and argumentative macropropositions and draws a parallel of the prototype of the argumentative sequence of each argumentative proposition to understand architecture of the editorial genre. In summary, this investigation aims to fill existing gaps, above all, in relation to the description and analysis of argumentative textual genres, more specifically the editorial ones, addressing them as social actions that showregularities, that is, they are relatively stable statements.